Bourdain [large type] : the definitive oral biography - Woolever, Laurie (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
The closest friends and colleagues of the late travel and food writer share their memories of his incredible life, from his early years in New York to his best-selling memoir "Kitchen Confidential" and emergence as a TV star